Socio-demographic characteristics, body weight status and energy intake among users and non-users of dietary supplements among government employees in Putrajaya, Malaysia - Mohd Ashri, Muhamad Hasrol; Abu Saad, Hazizi; Adznam, Siti Nur ‘Asyura (MDPI AG, 2021)
The use of dietary supplements is prevalent among many groups worldwide. However, few studies have examined their use among government employees. The aim of this cross-sectional study was to determine the association among sociodemographic characteristics, body weight status, and energy intake with dietary supplement use among government employees in Putrajaya, Malaysia. Simple random sampling was used to select a sample of 460 government employees from six ministries in Putrajaya, Malaysia. The data used in this study were collected through anthropometric measurements (height, weight, % body fat, waist and hip circumferences), a self-administered questionnaire (sociodemographic characteristics and dietary supplements use), and an interviewer-administered questionnaire (24-hour dietary recall; fruit and vegetable intake). The results indicated that the prevalence of dietary supplement use was 55.4%, with vitamin C (38.4%) being the most popular type of dietary supplement. Health issues (80.8%) were the most common reason for usage, internet (59.2%) was the main source of information, and pharmacies (71.8%) were the most indicated places to purchase dietary supplements. A multivariate analysis showed that participants who were female, married, had better monthly income, lived within a smaller household size, had a normal body mass index, classified as having unhealthily high body fat percentage, did not skip breakfast, and consumed at least five servings of fruits and vegetables per day were significantly more likely to use dietary supplements. In conclusion, health-conscious groups were more prone to consume dietary supplements, and due to the high prevalence of dietary supplement use, dissemination of accurate scientific information regarding dietary supplements is highly recommended among government employees.